2020
DOI: 10.1186/s12886-020-1307-7
|View full text |Cite
|
Sign up to set email alerts
|

Malapposition of graft-host interface after penetrating keratoplasty (PK) and deep anterior lamellar keratoplasty (DALK): an optical coherence tomography study

Abstract: Backgroud Previous studies of internal graft-host malappositions have not dealt with the precise ways in which each malapposition affected post-penetrating keratoplasty (post-PK) visual outcomes. In this study, we reviewed our post-PK and post-deep anterior lamellar keratoplasty (post-DALK) keratoconic patients and used anterior segment optical coherence tomography (AS-OCT) to evaluate the associations between graft-host interface (GHI) characteristics and visual outcomes. Methods Novel GHI metrics included: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…DALK in keratoconus aims to improve visual quality through the restoration of corneal morphology. The graft-host matching is a key factor to achieve optimal visual and refractive outcomes ( 16 ). The thickness of the corneal bed is also a factor that limits the visual acuity restoration after DALK, a recipient thickness of more than 80 μm reduces the post-operative visual acuity ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…DALK in keratoconus aims to improve visual quality through the restoration of corneal morphology. The graft-host matching is a key factor to achieve optimal visual and refractive outcomes ( 16 ). The thickness of the corneal bed is also a factor that limits the visual acuity restoration after DALK, a recipient thickness of more than 80 μm reduces the post-operative visual acuity ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is essential to note that the implant added volume to the retained peripheral recipient cornea ( Figure 5 ), decreasing the difference between the Tg and Th (Tg-Th). Zhao et al ( 16 ) found that the larger the (Tg-Th) value, the worse the visual and refractive outcomes. The (Tg-Th) value was lower in our study than that reported by Zhao et al ( 16 ) (45.1 and 85.74 μm, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations